Electrospinning and Electrospraying Techniques and Applications - Haider, Sajjad; Haider, Adnan (IntechOpen, 2019)
This book focuses on the recent advancements in the process parameters, research, and applications of electrospinning and electrospraying. The first chapter introduces the techniques and the effect of the parameters on the morphology of the nanofiber and nanoparticles and then the subsequent chapters focus on the applications of these techniques in different areas. This book will attract a broad audience including postgraduate students and industrial and academic investigators in sciences and engineering who wish to enhance their understanding of the emerging technologies and use this book as reference.